Self-esteem berperan terhadap kebahagiaan pada penggemar Anime - Dimas Permana Putra; Dyta Setiawati Hariyono; Gladis Corinna Marsha (Psychological Journal: Science and Practice, 2025)
This study examines the positive role of self-esteem in the happiness of anime fans who receive negative evaluations from their social environment and tend to withdraw, thereby hindering their ability to enjoy life’s pleasures. The objective of this research is to investigate the influence of self-esteem on the happiness of anime fans. A quantitative non-experimental design was employed, involving a sample of 87 anime fans. Happiness was measured using a happiness scale, while self-esteem was assessed with the Rosenberg Self-Esteem Scale. The results indicate a positive role of self-esteem on the happiness of anime fans, with a coefficient of 0.320. This suggests that higher self-esteem is associated with greater happiness among fans. Anime fans with higher self-esteem tend to experience a happier life despite facing negative social perceptions. Individuals with elevated self-esteem also demonstrate greater life satisfaction and more effective coping mechanisms, regardless of the negative views held by their social environment regarding their hobby. These findings highlight the importance of self-acceptance and positive self-perception for the well-being of anime fans.